2015
DOI: 10.15376/biores.10.4.6809-6818
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Surface Properties of Heat-Treated Phyllostachys pubescens Bamboo

Abstract: The wetting phenomena and surface energetic behavior in heat-treated bamboo were studied. The bamboo specimens were heat-treated at temperatures of 100, 140, and 180 °C for 4 h, and an untreated sample served as a control. The sessile drop technique was used to estimate the surface contact angles of the control and heat-treated bamboo samples. The contact angle data were then used to determine the surface free energies using the Lifshitz-van der Waals/acid-based approach. The results revealed that the heat tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
(13 reference statements)
3
12
0
1
Order By: Relevance
“…A reduction in the wettability property was observed after heat treatment of spruce, poplar, beech, pine (Petrissans et al 2003) and Pinus pinaster and Eucalyptus globules (Esteves et al 2007). Similar observations were found in Phyllostachys pubescens (Zhang and Yu 2015).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…A reduction in the wettability property was observed after heat treatment of spruce, poplar, beech, pine (Petrissans et al 2003) and Pinus pinaster and Eucalyptus globules (Esteves et al 2007). Similar observations were found in Phyllostachys pubescens (Zhang and Yu 2015).…”
Section: Introductionsupporting
confidence: 89%
“…The observations reported in the present study differed from the other studies. Previous studies by Hou et al 2011, Li et al (2015) and Zhang & Yu (2015) showed a significant increase in the contact angle after the thermal treatment of Phyllostachys pubescens. Similarly, an increase in contact angle was observed in beach wood (Hakkou et al 2005), spruce, poplar, beech and pine (Petrissans et al 2003), Pinus pinaster and Eucalyptus globules (Esteves et al 2007) after heat treatment.…”
Section: Effect Of Thermal Treatment On Wettability Property Of D Asmentioning
confidence: 77%
“…In terms of chemical components, the content of alpha cellulose, hemicellulose, starch, and sugar decreased, the content of extraction and lignin increased, the pH value decreased, and the hydroxyl and hydrogen bonds of the cell surface decreased [31]. As for performance, the unit surface free energy and polarity decreased, the density, volume shrinkage, and equilibrium moisture content decreased, the hydrophobicity increased, and the elastic modulus of fibroblast and parenchyma cell wall remained unchanged, and the hardness increased significantly [32][33][34]. In the course of the above changes, the formation of cracks and the increase of grain size are conducive to the subsequent penetration of PF resin into the microstructure of bamboo.…”
Section: Research Progress Of Bamboo Recombinationmentioning
confidence: 99%
“…The utilization of thermally modified wood for indoor or outdoor applications has progressively increased due to its above-mentioned advantages. Previous studies have reported that the surface of the wood after the TM shows some changes when compared to unmodified wood (Hakkou et al 2005;Zhang et al 2015;Miklečić and Jirouš-Rajković 2016;Hill et al 2021). These changes include a decreased wettability and an inactivation of the surface.…”
Section: Introductionmentioning
confidence: 98%
“…Some chemical reactions occur in the wood during the thermal treatment, e.g., hydrolysis and oxidation, which cause the reduction of free hydroxyl groups and surface inactivation (Hakkou et al 2005;Petric et al 2009;Miklečić and Jirouš-Rajković 2016). Previous studies reported that the surface inactivation caused by the TM influences the wettability, which plays a role in the bonding mechanism between wood and certain coatings (Jarusombuti et al 2010;Hubbe et al 2015;Zhang and Yu 2015). Coating systems need to spread and penetrate the surface of the wood for good bonding to occur.…”
Section: Introductionmentioning
confidence: 99%